PENINGKATAN PENDIDIKAN MASYARAKAT MINAHASA DAN DAMPAKNYA: TINJAUAN EKONOMI DAN SOSIAL* - Helmut Weber (Populasi, 1991)
According to statistical data, the participation of the Indonesian population in the formal educational sector is increasing rapidly. On the one hand, interms of quantity, this increase reflects a significant success of the Indonesian development polity. But on the other hand, the more or less uncontrolled growing number of highly educated (which does not directly means highly skilled) people also contains a multitude of problematical impacts on daily life, which are rarely discussed up to now. Based on a more quantitatively oriented case study, which has been carried out in the district Minahasa, North Sulawesi, we will discuss some aspects of social-economic change on the village level, mainly caused by the development of the educational sector. Among others, the following aspects will be scrutinized indetail: the aspiration of the village people, monopolized by, formal education, education as an influential a) on monetarization of the household economy, b) on land-distribution, c) on employment problems and the composition of the local labour force, d) onspatial mobility, and e) on investment behavior ont he houshold level. Beside these more economic items, some significant social impacts will also be discussed, such as the relation between education and individualization, the spatial distributionofthe family membersand its implications intermsof social; security, the differentiation of 'life-styles' and finally the alienation process between different generations.